Stated Preferences for Consumption of Sea Urchin: A Choice Experiment in Sardinia (Italy) - Roberto Furesi; Fabio A. Madau; Andrea Palomba; Pietro Pulina (International Journal on Food System Dynamics, 2014)
In Sardinia sea urchin (Paracentrotus lividus) roe is a basic ingredient for several dishes (e.g. pasta, pizza, croutons) and its demand is constantly increasing. However marketable value of local sea urchin appears to be potentially higher than the current value. This paper aims to estimate the value of a based sea urchin dish according to the stated preference of consumers. A Choice Experiment (CE) analysis on 475 consumers was carried out in order to estimate their willingness to pay (WTP) for consuming sea urchin. Seafood was proposed as alternative to sea urchin. CE concerned two attributes: certification of local origin and place where dishes are consumed. Findings suggest that WTP for a generic dish is significantly higher for sea urchin (11.65 Euros) than for seafood (7.94 Euros) based dish. Furthermore, we found that WTP is higher when both foods are consumed with spaghetti and as raw fresh product, whereas an opposite effect is associated to pizza. Finally, the influence of some socio‐economic characteristics of responders on their preferences was estimated.